Role of Remittance in Economic Development of Nepal (Swarnadwar, 2024)
The aim of this research paper is to analyze the impact of remittances in economic development of the country. The study is quantitative in nature and examines the impact of remittances on two economic development indicators: nominal Gross Domestic Product (GDP) and Per Capita GDP (PCI). This study employs both descriptive analysis and a simple linear regression model. The contribution of remittances to GDP was 10.28 percent in 2001/02 and increased to 22.68 percent in 2022/23. The impact of remittances has been seen positive on both indicators, GDP and PCI, but it is comparatively lower for PCI. The findings show that the relationship between remittances and GDP, as well as between remittances and PCI, is significant. This means remittances have been playing vital role in improving economic well-being and reducing poverty.